(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The principles of agriculture organization in land use and the importance of ecological-landscape approaches to the acceptability of geographical resources in the cultivation of agricultural crops are explained. The article expresses the main problems of the study of agro-landscapes, the interpretation of the concepts of agro-landscape by experts in the field, and the theoretical aspects of the scientific principles and approaches to research.